Quran's Insight On Human Rights - Salehuddin Matawang (Journal Of Social Science (JoSS), 2024)
This study focuses on the growing global debate about human rights and the role of religion, particularly Islam, in shaping these concepts. The research aims to analyze the Quran's perspective on human rights, identifying fundamental principles that affirm universal values such as justice, Freedom, and equality. This study employs a qualitative method with a textual analysis approach to relevant Quranic verses. The findings reveal that the Quran explicitly recognizes fundamental human rights, including the right to life, Freedom of religion, and protection from oppression. The discussion also highlights that a comprehensive and contextual interpretation of the Quranic verses is necessary to understand the Islamic perspective on human rights in the modern context. The study concludes that the Quran provides a solid ethical and moral foundation for human rights, but its application depends on proper interpretation by Muslim communities worldwide. The research suggests the need for further dialogue between religious traditions and international law to support the global protection of human rights.